2017
DOI: 10.1186/s40101-017-0128-8
|View full text |Cite
|
Sign up to set email alerts
|

Increase in brain activation due to sub-tasks during driving: fMRI study using new MR-compatible driving simulator

Abstract: BackgroundSeveral studies have used functional magnetic resonance imaging (fMRI) to show that neural activity is associated with driving. fMRI studies have also elucidated the brain responses associated with driving while performing sub-tasks. It is important to note that these studies used computer mouses, trackballs, or joysticks to simulate driving and, thus, were not comparable to real driving situations. In order to overcome these limitations, we used a driving wheel and pedal equipped with an MR-compatib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 24 publications
2
36
0
Order By: Relevance
“…Driving requires the coordination of multiple cognitive functions and recruitment of associated multiple brain regions. Several fMRI studies on various driving tasks have demonstrated the activation of widespread brain network including occipital, parietal, frontal, motor and cerebellar regions and others to maintain safe driving ( 4 8 ). Figure 1 shows an example of activated brain regions while driving in a recent fMRI study ( 4 ).…”
Section: Neural Basis Of Driving Ability In Healthy Individualsmentioning
confidence: 99%
See 3 more Smart Citations
“…Driving requires the coordination of multiple cognitive functions and recruitment of associated multiple brain regions. Several fMRI studies on various driving tasks have demonstrated the activation of widespread brain network including occipital, parietal, frontal, motor and cerebellar regions and others to maintain safe driving ( 4 8 ). Figure 1 shows an example of activated brain regions while driving in a recent fMRI study ( 4 ).…”
Section: Neural Basis Of Driving Ability In Healthy Individualsmentioning
confidence: 99%
“…Several fMRI studies on various driving tasks have demonstrated the activation of widespread brain network including occipital, parietal, frontal, motor and cerebellar regions and others to maintain safe driving ( 4 8 ). Figure 1 shows an example of activated brain regions while driving in a recent fMRI study ( 4 ). In their study, during driving only condition, the occipital activations were observed in the inferior, superior and middle occipital gyri and lingual gyrus.…”
Section: Neural Basis Of Driving Ability In Healthy Individualsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cortical activation is more symmetrical when drawing [12], with a more intense activation of right hemisphere regions related to language comparatively to writing [13]. Besides, there are verbs that express actions carried out with either hand, such as "hold" and "pull," whose central processing is also left-lateralized [14,15] and verbs that describe coordinated asymmetric bimanual activities such as "tie" and "drive", whose central processing is non-lateralized and more symmetrical [16][17][18]. Although all these manual action verbs describe activities performed by the right hand in right-handers, the possibility that they describe an activity performed by the left hand is variable.…”
Section: Introductionmentioning
confidence: 99%